Механизм инициирования динамических явлений в подготовительных забоях - Ержанов Ж. С. Жакан Сулейменович; Векслер Ю. А. Юлиан Абрамович; Жданкин Н. А. Николай Александрович; Колоколов С. Б. Сергей Борисович (Алма-Ата, Наука, 1984)
Авт. указаны на обороте тит. л.